A Scoping Review for Strategies to Increase Living Kidney Donation - Barnieh, Lianne (Clin J Am Soc Nephrol, 2017)
BACKGROUND AND OBJECTIVES: The literature on strategies to increase the number of potential living kidney donors is extensive and has yet to be characterized. Scoping reviews are a novel methodology for systematically assessing a wide breadth of a given body of literature and may be done before conducting a more targeted systematic review. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We performed a scoping review and summarized the evidence for existing strategies to increase living kidney donation. RESULTS: Our review identified seven studies that tested interventions using rigorous methods (i.e., randomized, controlled trials) and outcome measures, all of which focused on using education targeted at potential recipients to increase living donation. Of these, two studies that targeted the potential recipients’ close social network reported statistically significant results. Other interventions were identified, but their effect was assessed through quasiexperimental or observational study designs. CONCLUSIONS: We identified an important gap in the literature for evidence-based strategies to increase living kidney donation. From the limited data available, strategies directed at potential recipients and their social networks are the most promising. These results can inform transplant programs that are considering strategies to increase living kidney donation and highlight the need for conduct of high-quality study to increase living donation.